Pengaruh Struktur Modal, Ukuran Perusahaan dan Profitabilitas Terhadap Nilai Perusahaan Perbankan yang Tercatat di BEI pada 2020-2022 - Elva Elfiana; Susilaningtyas Budi Kurniawati; Supartini (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2024)
This study aims to examine the effect of capital structure, company size and profitability on the value of banking sector companies. Capital structure variables are proxied with Debt to Equity Ratio (DER), company size variables are proxied with natural logarithms of total assets, profitability is proxied by Return on Equity (ROE) and company value is proxied by Price to Book Value (PBV). In this study using a verifiative descriptive research method with a quantitative approach. The data in this study is secondary data obtained from the Indonesia Stock Exchange. The sample used was 138 out of 46 banking companies listed on the Indonesia Stock Exchange in 2020-2022. The data processing technique uses multiple linear regression analysis using SPSS version 25. The results of this study show that capital structure has no effect on the value of the company. While the size of the company and profitability affect the value of the company.